Human Right to Citizenship in International Conventions and Omani Legislation: Comparative Study - Mahdi, Najm; Alkalbani, Hamad (Journal of Legal Sciences, 2023)
The idea of citizenship is one of the old political and legal ideas that have long occupied a wide area of thinking in most countries of the world because the right of citizenship is linked to the identity and cultural reference of human persons of different origins and ethnicities. Citizenship is the equality of citizens irrespective of religious, sectarian, tribal, ethnic, or sexual tinctures. Countries sought to enshrine this right through international conventions, affirmed through the constitutions, statutes, laws, and media of States, to increase the association of individuals affiliated with the State with their national identity and to grant these individuals all their rights under international conventions, constitutions, or domestic laws as an important element of the State. Citizenship in its sense remains an inclusive framework. This right safeguard the rights of the minority and the majority within the scope of the concept of inclusive citizenship. The citizen has all the rights and duties, and real citizenship does not ignore the realities of the country's cultural, social, and political composition.The rights enshrined in the Universal Declaration of Human Rights and international human rights conventions have affirmed the utmost importance of every individual in society. This right has been enshrined in the constitutions of States, including the Basic Law of the State of the Sultanate of Oman.